Decisões de terceirização e as práticas em gestão do fator humano: análise nas grandes indústrias cearenses de confecção - Souza, Leonardo Leocádio Coelho de (2005)
The objective of this paper is to research and present the motives which sustain the decisions of outsourcing in the clothing producers in the state of Ceará. It also aims at qualitatively evaluating the practices of managing the human factor in outsourcing. Initially, technical approaches were made such as: organizations in networks and strategic contracting out; business strategy and managing the human element; the textile industry and the clothing sector. After looking over the bibliography, a field survey was taken using two semi-structured questionnaires and a guided interview in the larger clothing manufactures in Ceará. After this, the information gathered was dealt with quantitatively and qualitatively. To do this the reversibility model was utilized. The survey enabled us to show that the decision to outsource, on the part of the companies surveyed, had a limited effect due to the inability to reduce costs and to the fact that quality was compromised. In this case, the fragility of the techniques in managing the human element in outsourcing is notorious. Although decisions to contract out are based, in general, on strategic criteria, the congruency between these decisions and the practices of managing the human element when outsourcing was not evident in the larger clothing producers in Ceará. It is believed that investment in the technology of managing work which is outsourced could correct the dysfunctions which were perceived.